Building Agricultural Extension Capacity in Post-Conflict Settings - McNamara, Paul (CABI, 2017)
This book investigates the experiences and issues involved with extension systems in post-conflict settings; evaluates the impact of different extension policy approaches and practice in such settings; and identifies the key elements needed to effectively rebuild agricultural extension systems and programs in post-conflict contexts. The chapters contain country-specific case studies that provide a descriptive account but also analyze strategies, successes and failures, and lessons learned. A synthesis chapter provides comparative analysis of insights across post-conflict settings. Overall, the book serves as a collective volume for use by governments, practitioners, and academics in extension policy-making and programming, and contributes to post-conflict, political science, and agricultural extension literature.